“Healing the Healer: A Case Report of Recovery from Severe Depression in an Experienced Yoga Prana Vidya (YPV) Practitioner” - Kumkum Saxena; Dr Shalini C (International Journal of Medical Science and Clinical Research Studies, 2026)
Depression is a major mental health disorder influenced by biological, psychological, and social factors. Family conflict, lack of social support, and loss of purpose can increase vulnerability to depression. Yoga Prana Vidya (YPV) is an integrated complementary healthcare system that combines rhythmic breathing, meditation, physical exercises, forgiveness practices, no-touch energy healing, and healthy lifestyle practices. This case report describes the recovery of a 58-year-old female long-term YPV practitioner who developed severe depression with suicidal ideation, anxiety, hypertension, thyroid dysfunction, chronic fatigue, generalized body pain, and significant weight loss (44 kg to 37 kg) following prolonged family resistance to her healing activities, social isolation, and inadequate nutritional intake. Despite profound physical and emotional distress, she remained connected to YPV by attending daily online Morning Sadhana and Divine Group Healing sessions. She reported that hearing the Guru's message, "No one needs you, but the Guru needs you. Work for Him," restored her sense of purpose and motivated her to actively re-engage in spiritual practices. Along with continued conventional medical treatment, improved nutrition, healing support from fellow practitioners, and participation in a two-month residential YPV program at YPV Ashram, Sri Ramana Trust, her condition improved substantially. Within six months, her weight increased to 54 kg, blood pressure stabilized at 129/75 mmHg, thyroid function normalized, chronic pain markedly reduced, and her psychological wellbeing improved. This case highlights the complex interaction of psychosocial stressors, spiritual coping, conventional medical care, nutritional rehabilitation, and social support in recovery from severe depression. It suggests that Yoga Prana Vidya may serve as a complementary approach to enhance resilience and functional recovery when integrated with standard medical management.